2017
DOI: 10.4103/ijpvm.ijpvm_36_17
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with screen time in Iranian children and adolescents: The CASPIAN-IV study

Abstract: Background:Prolonged screen time is frequent in children and adolescents. Implementing interventions to reduce physical inactivity needs to assess related determinants. This study aims to assess factors associated with screen time in a national sample of children and adolescents.Methods:This nationwide study was conducted among 14,880 students aged 6–18 years. Data collection was performed using questionnaires and physical examination. The World Health Organization-Global School Health Survey questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
(67 reference statements)
2
9
0
Order By: Relevance
“…Despite some recent advancement in understanding the complex relationships, studies examining associations between physical activity, sedentary behavior and insomnia among adolescents in the low-and-middle-income countries (LMICs) are scarce. In the only nation-wide study to date, screen time among adolescents from Iran was higher in those with insomnia (Mozafarian et al, 2017). Second, it remains to be explored in more detail how much time spent sitting and how much time spent watching TV are associated with insomnia and how much time spent physically active might be protective.…”
Section: Pharmacotherapy Might However Have Side-effects While a Commmentioning
confidence: 99%
“…Despite some recent advancement in understanding the complex relationships, studies examining associations between physical activity, sedentary behavior and insomnia among adolescents in the low-and-middle-income countries (LMICs) are scarce. In the only nation-wide study to date, screen time among adolescents from Iran was higher in those with insomnia (Mozafarian et al, 2017). Second, it remains to be explored in more detail how much time spent sitting and how much time spent watching TV are associated with insomnia and how much time spent physically active might be protective.…”
Section: Pharmacotherapy Might However Have Side-effects While a Commmentioning
confidence: 99%
“…They are both suggested as unhealthy behaviors which their longitudinal trends could continue into adulthood [12]. Previous studies have mentioned low PA and high ST in Iranian children and adolescents [1316], as the mean of vigorous PA in Iranian adolescents and children was estimated to be 0.6 h/d in one study [17, 18]. Increased ST is an indicator of sedentary behaviors, and expresses situations with low energy expenditure of energy [19], namely the time spent watching television (TV), playing video games and leisure time computer work.…”
Section: Introductionmentioning
confidence: 99%
“…There was no uniform standard for prolonged screen time. We referred to a previous study that defined prolonged screen time as daily screen time of more than four hours [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence has suggested that prolonged screen time might be associated with higher income, non-intact family, urban residence, being male, poor sleep quality, bad self-reported health status, and obesity [ 26 , 27 , 28 ]. Despite important work in this area, the majority of current studies focus on screen time and the use of electronic devices before sleep among children and adolescents.…”
Section: Introductionmentioning
confidence: 99%